A ratio Tauberian theorem - Abu-Khzam, Faisal N. (1996)
Let f be a given function and Tf some integral transform of it. The question of deducing the asymptotic behavior of - from that of Tf is classical and has received much attention. More recently the question of deducing the asymptotic behavior of f from t.